The Impact of Social Media on the Learning Process of Children Aged 6-12 Years Old - Wahyuni, Ni’mah; Putri, Ditta Kristina; Widiyastuti, Sri; Siburian, Henry Kristian; Saputra, Dedi Gunawan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
In the current era of globalization, technology is something that is indispensable and even used every day, both in long-distance activities, education, work, socialization, and even entertainment such as playing online games, not even a few children who see negative video channels on social media. So the fact is that currently social media does have a big influence on a person's life, both negative and positive impacts. One of them is for children aged 6-12 years. At school, children also prefer to play social media rather than interact and play with children their age. The purpose of this study was to determine the impact of social media on the learning process of children aged 6-12 years. This research uses quantitative methods, data used through online interviews and distributing questionnaires through the use of google froom. The results of this study explain that social media is very influential on children's learning both at school and children's learning at home. So that children's time in learning becomes less effective because they are too busy playing social media, due to lack of supervision from parents. The conclusion from the results of this study explains that the impact of social media on the learning process of children aged 6-12 years is very influential on the child's learning process. The limitation of this study is that researchers only conducted research in one school in the Batanng anai sub-district of West Sumatra province. Researchers hope that this research process can be useful for readers and other parties. this study also recommends that other studies make references related to the impact of social media on the learning process of children 6-12 years.